Boswellia serrata Extract Containing 30% 3-Acetyl-11-Keto-Boswellic Acid Attenuates Inflammatory Mediators and Preserves Extracellular Matrix in Collagen-Induced Arthritis - Majeed, Muhammed; Nagabhushanam, Kalyanam; Lawrence, Lincy; Nallathambi, Rameshprabu; Thiyagarajan, Varadharajan; Mundkur, Lakshmi (Frontiers in Physiology, 2021)
Boswellia serrata extracts have been traditionally employed for the treatment of inflammatory diseases. In the present study, we have evaluated the mechanism of activity of Boswellin Super® (BSE), a standardized extract of Boswellia serrata containing not less than 30% 3-acetyl-11-keto-β-boswellic acid along with other β-boswellic acids. The in vitro anti-inflammatory activities were carried out in RAW 264.7 macrophages or human peripheral blood mononuclear cells stimulated with bacterial lipopolysaccharides (LPS) and treated with 1.25-5µg/ml BSE. The anti-arthritic activity of the extract was evaluated in a rat model of collagen-induced arthritis. BSE at 40 and 80 mg/kg, and celecoxib 10 mg/kg were orally dosed for 21 days. BSE showed significant (p<0.05) inhibition of inflammation (TNF-α, IL-6, nitric oxide, and COX-2 secretion) and downregulate the mRNA levels of TNF-α, IL-6, IL1-β, and inducible nitric oxide synthase in macrophages. BSE treatment reduced the levels of phosphorylated NF-κB (P65), suggesting an anti-inflammatory activity mediated by blocking this key signal transduction pathway. In addition, BSE showed inhibition (p<0.05) of collagenase, elastase, hyaluronidase enzymes and a reduction in reactive oxygen species and matrix-degrading proteins in RAW 264.7 macrophages stimulated with LPS. BSE treatment significantly(p<0.05) reduced the arthritic index, paw volume, and joint inflammation comparable to celecoxib in collagen-induced arthritis (CIA) in rats. The circulating anti-collagen antibodies were reduced in BSE and celecoxib-treated animals as compared to the CIA. In confirmation with in vitro data, BSE showed a significant (p<0.05) dose-dependent effect on C-reactive protein, Prostaglandin E2, and Erythrocyte sedimentation rate (ESR), which is widely used as a blood marker of inflammation. Further, BSE treatment suppressed the Cartilage oligomeric matrix protein (COMP) and significantly enhanced the hyaluronan levels in synovial fluid. As observed by collagen staining in joints, the loss of matrix proteins was lower in BSE-treated animals, suggesting that BSE could preserve the extracellular matrix in RA. The extract showed inhibition of collagenase enzyme activity in vitro, further strengthening this hypothesis. BSE treatment was found to be safe, and rats displayed no abnormal behavior or activities. The results suggest that Boswellin Super® mediates its activity by preserving matrix proteins, reducing pro-inflammatory mediators and oxidative stress.